Multiplex PCR in non-human DNA molecular identification of Ascaris spp. in forensic biology. (December 2017) - Burgos, G.; Yanqui-Rivera, F.; Mollocana, D.; Camargo, M.; Zapata, S.; Arahana, V.; Paz-y-Miño, C.
Abstract: Forensic parasitology is a promising new tool to prevent illegal trade in protected species, and other research areas like epidemiology and human public health protection. Two multiplex PCR maps for 14 microsatellites loci were designed based on information content reported in Ascaris spp. literature. PCR reactions were standardized, minimizing artefacts, to obtain genetic profiles that allowed discrimination between individuals. This protocol is an alternative to replace current STRs monoplex genotyping techniques; it permits the optimization of resources, improving specificity and sensitivity compared with common methods used to typify this parasite.